A critical review on the application of the National Sanitation Foundation Water Quality Index. (January 2019) - Noori, Roohollah; Berndtsson, Ronny; Hosseinzadeh, Majid; Adamowski, Jan Franklin; Abyaneh, Maryam Rabiee
Abstract: Many studies have employed the National Sanitation Foundation Water Quality Index (NSFWQI) with non-original rather than originally defined parameters of the model, particularly when incorporating fecal coliform (FC), total solids, and total phosphates as inputs. For this reason, this study aimed to perform a critical review on the application of the NSFWQI to explore the amount of change that can be expected when users employed non-original parameters (such as orthophosphate and total dissolved solids/total suspended solids instead of total phosphorous and total solids, respectively), or different units (FC based on the maximum probable number (FC-MPN) rather than the colony forming unit (FC-CPU)). To demonstrate the influence of originally defined inputs on NSFWQI results, various scenarios were investigated. These scenarios were generated using different possible inputs to the NSFWQI, altering the FC, total solids, and total phosphorous parameters obtained from the monitoring stations of the Sefidroud River in Iran. Considerable differences were observed in the NSFWQI values when using orthophosphate and total suspended solids, instead of the originally defined data (i.e., total phosphorous and total solids), in the model (first scenario). In this case, the number of stations with "good" water quality increased from one to seven when compared with the first scenario results. In addition, unlike the results of the first scenario, none of the stations were classified as class IV (i.e., "bad" water quality status). However, the results of the implemented scenarios presented a more favorable water quality status than those obtained using the first scenario (except the second scenario which included FC-MPN rather than FC-CFU). Using total dissolved solids instead of total solids and FC-MPN rather than FC-CPU, resulted in fewer changes. In both cases, the average of the NSFWQI values in the river classed all stations as "medium" and "bad" water quality for the wet and dry seasons, respectively. Proper application of NSFWQI is important to provide high quality results for evaluation of water bodies, particularly when incorporating total solids and total phosphorous as inputs. Graphical abstract: Image 1 Highlights: NSFWQI is widely used with non-original rather than original inputs of the model. How much change is expected if the user employed non-original inputs to the model. Six scenarios explored to assess effects of non-original inputs on NSFWQI results. The scenarios included the use of different possible inputs to the NSFWQI. Findings show changes in NSFWQI results under multiple input application scenarios. Abstract : The findings showed substantial changes in NSFWQI results when using orthophosphate and total suspended solids instead of total phosphorous and total solids, respectively. Using total dissolved solids instead of total solids and FC-MPN rather than FC-CPU, resulted in fewer changes. Generally, results indicated that the river water quality status in the wet season was better than during the dry season so that none of the scenarios classified the river water quality as "bad" (in terms of water quality status) in the wet season. Meanwhile, the river water quality was classified as "bad" for three scenarios in the dry season.